Feasibility of endovascular aortic arch repair after hemiarch replacement for acute type A aortic dissectionCentral MessagePerspective - Srihari K. Lella, MD; Matthew J. Eagleton, MD; Thoralf M. Sundt, III, MD; Sunita D. Srivastava, MD; Motahar Hosseini, MD; Jordan P. Bloom, MD, MPH; Antonia Kreso, MD, PhD; Serguei Melnitchouk, MD, MPH; Jahan Mohebali, MD, MPH; Arminder S. Jassar, MBBS, FRCS (JTCVS Structural and Endovascular)
Objective: We assessed the treatment feasibility of 4 investigational arch endografts currently available in the United States, for patients who have undergone hemiarch replacement for an acute DeBakey I dissection. Methods: We evaluated 71 consecutive patients for suitability for treatment with the Cook Medical Zenith Arch Branched Device, Gore TAG Thoracic Branch Endoprosthesis, Terumo Bolton Relay Dual Branch Device, and Endospan Nexus Aortic Arch Stent Graft System. Proximal landing zone anatomy was evaluated on postoperative computed tomography angiography using 3-dimensional imaging software and compared against each manufacturer recommended sizing criteria. Results: Twenty-one patients (29.6%) were deemed unsuitable for branched endograft due to mechanical aortic valve, connective tissue disorder, and extension of dissection into the brachiocephalic trunk (BCT). Forty-one percent were excluded from all devices; 8.5% were candidates for only 1 device, 24% for 2, 4% for 3, and 23% for all 4 devices. Reasons for exclusion included ascending aortic/neck diameter being too large/small, insufficient ascending aorta length, insufficient BCT length, and BCT size being too large. Both patient-related factors (BCT diameter/length, dissection into BCT, and connective tissue disorder) and technical factors (mechanical aortic valve, ascending aorta graft length/diameter) influenced candidacy. Conclusions: Despite the availability of multiple branched endovascular devices, a significant number of patients may be unsuitable for subsequent endoarch repair. Awareness of anatomic inclusion criteria for arch endografts and modification of surgical technique for creation of a suitable landing zone at the initial operation may increase the likelihood of successful endovascular repair in the future.